STRATEGI GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENGINTERNALISASI NILAI-NILAI RELIGIUS DI SDN TEGALWARU 3 KECAMATAN CILAMAYA KARAWANG - Supriyatno Supriyatno; Ibnu Muthi; Asep Dudin Abdul Latif (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The enactment of learning during the covid 19 emergency period is something that is good for teachers, Students or parents of students, The impact on the decline in the quality of student learning outcomes includes cognitive achievement and the values of students' religious character. This research aims to find out: Strategy teacher of Islamic Religiou Education and ethics in internalizing religious of value in student, Religious values practiced by SDN Tegalwaru 3 Students durimg the period of covid 19 pandemic, as well as supporting factors and inhibiting efforts to imralize religious of value in SDN Tegalwaru 3. Value internalization is the process of making value a part of a person. Strategy is a learning strategy carried out by teachers according to their duties as professionals with the main task of educating, teaching, guiding, directing, training, appraise, and evaluating learners.The research focused on 1 elementary school located in the Kab. Karawang area, namely in SDN Tegalwaru , this research using qualitative research, with case study methods, A research procedure that produces descriptive data in the form of written or oral data from people and behaviors that can be observed as the object of research. Concluded the Strategy of Islamic Teacher Education and internalizing ethichs the religious values of students, consists of several stages, this is: the first, The stage of Transformation value, A process of informing good and unfavorable values to students, the secound, the stage of transaction value, namely the stage of education values two-way communication, or interaction between learners and educators is reciprocal. Implementation through it, the phase Receiving Students listen to every piece of advice and the Responding Stage. Internalization of Students & Religious Values Outside of Study Hours, Through Counseling and Home Visit. Supporting Factors for Principal Commitment, Support of All Teachers, Support parents of students of the Community of Students Live, Children's environment near places of worship (Mosque) and Dokungan Ustad and the community around the school. Inhibitory Factors: Minimal Means, Weak Mastery of Technology, Low levels of Economy and Education Parents to Students, Limited Teacher Time and Budget Limited School. Advised by the principal, the teacher maintains his work in building and realizing a religious and responsible school to various school programs related to the internalization of students; religious values.